Analysing the equity dimensions and governance drivers of water security challenges in Hammanskraal, City of Tshwane, South Africa - Mahlatsi, Malaika Lesego Samora (Rhodes University, Faculty of Science, Institute for Water Research)
South Africa is faced with a national water security challenge that is increasingly worsening due to a myriad of structural and governance factors. Over the past few years, several municipalities across the country have experience temporary loss of water access, while some have come dangerously close to Day Zero "“ a day when water levels of the major dams supplying water to residents would become critically low, resulting in households having no running water. But for the people of the township of Hammanskraal in the City of Tshwane metropolitan municipality, water insecurity has reached crisis point. Since 2005, the township has been battling with a chronic lack of access to safe drinking water. The water quality in Hammanskraal has been so dire that in 2019, the South African Human Rights Commission declared it unfit for human consumption and deemed it a violation of human rights. Despite this, the crisis has persisted. In 2023, Hammanskraal became the epicentre of a cholera outbreak that claimed a number of lives in several provinces across the country. Using a qualitative approach, this study analyses the equity dimensions and governance drivers of water security challenges in Hammanskraal. Through interviews with residents in Hammanskraal and government officials in the City of Tshwane metropolitan municipality and the Gauteng Provincial Government, the study explores the lived experiences of those affected by the water insecurity, as well as the governance drivers that inform the crisis. The study, using water justice theory and conflict theory/Marxism, contends that the water security challenges in Hammanskraal are driven by physical, economic and political factors. These factors have their roots in the geo-history of the township as well as contemporary responses to spatial development and water resource management by the post-apartheid government. The study finds that there are equity dimensions to the water security challenges in Hammanskraal. Contextually, the legacy of apartheid's policy of separate and uneven development, coupled with contemporary failings of the implementation of the National Water Act, impact water access. In terms of water governance, while factors such as climate change and urbanisation are contributing determinants, the water security challenges in Hammanskraal are fundamentally the result of institutional failings that include lack of planning and investment as well as lack of infrastructure maintenance. The implications for South Africa in general is that failure to resolve water inequities and to strengthen water governance will result in the reproduction and persistence of structural inequalities. Key recommendations of the study include the expansion of the Temba Water Purification Plant, strengthening and coordination of institutions for water security, the setting of water allocation ceilings in Gauteng municipalities and investment in alternative water sources and tools for water conservation. The study also recommends further study into the extent to which water security challenges impact social unrest in South Africa.
Keywords: Water security -- South Africa -- Hammanskraal; Water governance; Water-supply -- Law and legislation -- South Africa -- City of Tshwane Metropolitan Municipality; Water quality -- South Africa -- Hammanskraal; Water-supply Management; South Africa -- Social conditions